Determinants of adoption and adaptation of sustainable agricultural practices by small coffee farmers in Luya, Amazonas – Peru - Guevara Fernández, Elen Francisco (2023)
Despite the benefits of Sustainable Agricultural Practices (SAPs) their use rate among smallholder farmers is still low in developing countries like Peru. This study sought to examine the factors that determine the adoption of SAPs and their intensity at the smallholder household level in four coffee producer districts of Luya, Amazonas – Peru, based on cross-sectional data obtained from 145 sampled households, six coffee farmer interviews, and three expert interviews. The study results showed that coffee farmers adopted SAPs according to distinct factors that determine or influence their uptake; those factors could be farm(er)-related, sustainable practice attributes, and exogenous factors. While it is true that there was no strict pattern in farmers’ profiles, especially in terms of socioeconomic characteristics, to explain the adoption of SAPs. Moreover, drawing on the logistic regression technique, the marginal effects of the key factors that determine the adoption of SAPs were obtained, the number of people of working age living in the household, educational attainment, number of assets, coffee yield, coffee price, farm investment, sustainable practices attributes, certification, farmer knowledge about sustainable practices, access to extension services, performance expectancy, and facilitating conditions. The main barriers to the adoption of bundled sustainable practices are the scarce labour availability during peak season, smallholders’ low economic level and lack of access to agricultural credit. These suggest that to improve sustainable practices adoption rates, it should be increased farmers’ knowledge about sustainable practices’ attributes through demonstration facilities and offer facilitating conditions like information, demand-driven research, seeking attributes that producers are interested in, access to a platform of coordinated extension and advisory services and input accessibility. To overcome the barriers, it is needed to enhance the accessibility to agricultural credit for farm investment and improvement of the work system to lower production costs through saving in labour force.